2004
DOI: 10.1002/chin.200502118
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activities of Some New 1‐(5‐Phenylamino‐[1,3,4]thiadiazol‐2‐yl)methyl‐5‐oxo‐[1,2,4]triazole and 1‐(4‐Phenyl‐5‐thioxo‐[1,2,4]triazol‐3‐yl)methyl‐5‐oxo‐[1,2,4]triazole Derivatives.

Abstract: With the aim to find novel antimicrobial and anticancer agents, a variety of 5-oxo-[1,2,4]triazoles [cf. compounds (IV), (VI), (VII), and (VIII)] is synthesized and evaluated. Derivatives (IVa-c), (VII), and (VIIIa,c) possess antimicrobial activity, while compound (IVd) is active against the MCF7 breast cancer cell lines. -(DEMIRBAS*, N.; KARAOGLU, S. A.; DEMIRBAS, A.; SANCAK, K.; Eur. J. Med. Chem. 39 (2004) 9, 793-804; Dep. Chem., Karadeniz Tech. Univ., TR-61080 Trabzon, Turk.; Eng.) -R. Staver 02-118

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…1,2,4-Triazoles showed antiviral, anti-inflammatory and antinociceptive properties (19) , anticancer (20) and antibacterial activity (21) .…”
Section: Abstract Introductionmentioning
confidence: 99%
“…1,2,4-Triazoles showed antiviral, anti-inflammatory and antinociceptive properties (19) , anticancer (20) and antibacterial activity (21) .…”
Section: Abstract Introductionmentioning
confidence: 99%
“…Demirbas et al, (2004) have reported Synthesis and antimicrobial activities of some new 1-(5-phenylamino-[1,3,4]thiadiazol-2-yl)methyl-5-oxo-[1,2,4]triazole and 1-(4-phenyl-5-thioxo-[1,2,4]triazol-3-yl)methyl-5-oxo-[1,2,4]triazole derivatives, Acetic acid ethyl esters containing 5-oxo-[1,2,4]triazole ring (2) were synthesized by the condensation of compounds 1a-f with ethyl bromoacetate in basic media. The reaction of compounds 2a-f with hydrazine hydrate led to the formation of acid hydrazides (3a-f).…”
mentioning
confidence: 99%